Online Fir Registration and Sos System (International Journal of Engineering and Computer Science, 2017)
This paper is on the project ‘Online FIR registration and SOS system’. The system Online FIR registration and SOS project is the first of its kind .It is designed to bridge the gap between the police and the common people. There are plenty of applications nowadays for shopping, travel and even for gaming purposes. However there is no application for the purpose of registering FIR or for helping the people while facing emergency situations. We intend to create a system where the users could register an FIR under various IPC sections and inform the police whenever in an emergency situation.  We believe this will be a widely used system in the future and will help to bridge the gap between the police department and the people.